2006
DOI: 10.1002/mrm.20993
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave group velocity inversion in MR elastography of human skeletal muscle

Abstract: In vivo quantification of the anisotropic shear elasticity of soft tissue is an appealing objective of elastography techniques because elastic anisotropy can potentially provide specific information about structural alterations in diseased tissue. Here a method is introduced and applied to MR elastography (MRE) of skeletal muscle. With this method one can elucidate anisotropy by means of two shear moduli (one parallel and one perpendicular to the muscle fiber direction). The technique is based on group velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 32 publications
5
98
0
Order By: Relevance
“…Regions in the vicinity of the brain surface appear to be softer than central brain parenchyma, which supports observations (32,33) that white brain matter is stiffer than gray matter. However, according to the literature, shear waves near the surface are affected by diffraction or non-evanescent (non-propagating) waves, eventually leading to biases in the estimated local wavelengths (43)(44)(45)(46). This conclusion justifies our approach of focusing on global measures, as shown in Figs Table 1.…”
Section: Resultssupporting
confidence: 64%
“…Regions in the vicinity of the brain surface appear to be softer than central brain parenchyma, which supports observations (32,33) that white brain matter is stiffer than gray matter. However, according to the literature, shear waves near the surface are affected by diffraction or non-evanescent (non-propagating) waves, eventually leading to biases in the estimated local wavelengths (43)(44)(45)(46). This conclusion justifies our approach of focusing on global measures, as shown in Figs Table 1.…”
Section: Resultssupporting
confidence: 64%
“…To overcome this limitation, future studies should include diffusion tensor imaging in order to derive the local frame of elasticity in each voxel (24,33). Of note, the curl-operator accounts for the directionality of shear waves by separating those curl components related to all three TI material parameters m In this way, Equation [13] includes the directional filters, which are applied separately otherwise (20,24). It is encouraging that the ratio between the shear moduli parallel and perpendicular to the fiber direction reported in a study combining MRE and DTI by Green et al (21) are similar to our ratios m More studies are warranted on the interaction of anisotropic viscoelasticity parameters with muscle load as well as on the observed laterality.…”
Section: Discussionmentioning
confidence: 99%
“…Explicit expressions for the shear wave modes in an incompressible TI material can be found in the literature (20):…”
Section: Shear Waves In Transversely Isotropic Mediamentioning
confidence: 99%
“…The potential of dynamic MRE clinical implementation has been proven in preliminary human studies in which the data of human prostate, breast, brain, muscle, and liver were presented (Bensamoun et al 2006;Bishop et al 1998;Kemper et al 2004;Kruse et al 2000;Papazoglou et al 2006;Rouviere et al 2006;Sinkus et al 2005). In particular, Kruse et al (2000) evaluated porcine livers with MRE at multiple shear wave frequencies and reported that the wave velocity and the shear stiffness increased with frequency.…”
Section: Introductionmentioning
confidence: 99%